Design and Simulation of Wideband Monopole Microstrip Antenna - Lalitha Bhavani Konkyana, Nelapati Ananda Rao, M. Lakshmu Naidu (Mathematical Statistician and Engineering Applications, 2022)
The paper explicates an optimal antenna using a monopole with defective ground plane for wideband operation. The radiator is an etched square with square slots at the corners and is intended for radio communication. To realize wideband operation and to improve the gain of the antenna defected ground arrangement is utilized. Finite element method is used to analyze the presented design. This radiator can show maximum response at four different operating frequencies in the frequency range of 3X103MHz to 9X103 MHz and presents the gain of 9.06dB, 3.83dB, 3.48dB,4.40dB at 3.0X103 MHz, 5.5X103 MHz, 6.9X103 MHz,9.1X103 MHz respectively. The radiator which is designed in the current work is implemented for many uses like wireless broadband implementation applicable to stable wireless communications, WLAN, remote sensing/fixed metrological and satellite communications. The HFSS simulation tool is employed to simulate the developed antenna design.